Assessment on mechanical properties of concrete with polypropylene fiber. Issue 1 (1st March 2022) - Jayaram, M; Naresh, J; Thipparthi, Karhik; Kastro Kiran, V
Abstract: Concrete is a versatile material that must meet certain strength criteria to maintain structural integrity. Although concrete has several advantages in terms of mechanical qualities and construction costs, its brittle nature is a drawback in those applications that require flexibility. However, the recent creation of concrete with polypropylene fiber-reinforced (PFRC) has provided a technical framework for addressing these issues. Polypropylene fibres have a tendency to bind the concrete mix. This reduces the rate of bleeding by slowing the settlement of coarse material. A slower rate of bleeding equals a slower rate of drying, which means less shrinkage breaking in the plastic. Polypropylene fibres act as crack stoppers in hardened concrete. The impact of polypropylene (PP) fibres on compressive strength, tensile strength, flexural strength, and workability for M 25 Grade concrete in both fresh and hardened states is investigated in this study. Polypropylene fibres were introduced at a percentage of 0.5%, 1%, 1.5 %, and 2% in this investigation, and the findings were tabulated.